Mechanical characterization of metal-ceramic composites - G. Bolzon; M. Bocciarelli; E.J. Chiarullo (Fracture and Structural Integrity)
Metal-ceramic composites represent a class of quasi-brittle materials for advanced structural applications that require adequate mechanical characterization. Difficulties and costs associated with material production and specimen extraction prevent the execution of a statistically meaningful number of standard laboratory tests. Parameter calibration methodologies based on instrumented indentation and inverse analysis represent fast and reliable identification procedures in the present context, as shown by the present contribution, based on some experience achieved in the framework of the European Network of Excellence on ‘Knowledge-based Multi-component Materials for durable and safe performance’ (KMM-NoE).